Screening and anti-virulent study of N-acyl homoserine lactones DNA aptamers against Pseudomonas aeruginosa quorum sensing - Zhao, Zu Guo; Yu, Yun Mei; Xu, Bi Yu; Yan, Shuang Shuang; Xu, Jun Fa; Liu, Fang; Li, Guo Ming; Ding, Yuan Lin; Wu, Shu Qing (Biotechnology and bioprocess engineering, 2013)
In Pseudomonas aeruginosa, a quorum sensing (QS) system regulates the expression of many virulence factors. N-acyl homoserine lactone (HSL) is the signal molecule of QS system. In order to find a novel HSL binder to interfere with QS signaling and to attenuate P. aeruginosa virulence, an amino lactam surrogate (ALS) of HSL was used as a target to screen HSL aptamers with the technique of systematic evolution of ligands by exponential enrichment (SELEX). Eight HSL aptamers with high affinities for 3O-C12-HSL (20 nM ≤ K d < 35 nM) or C4-HSL (25 nM < K d < 50 nM) were finally obtained. In vitro QS-inhibiting study of P. aeruginosa showed that HSL aptamers could inhibit virulence in a dose-dependent manner. ALSap-8 which bound C4-HSL primarily acted on the rhl system and inhibited the secretion of pyocyanin. ALSap-5 which bound 3O-C12-HSL not only showed strong inhibitory activity on biofilm formation as well as secretions of LasA protease and LasB elastase, but also reduced pyocyanin secretion. Since the las system is capable of activating the rhl system mildly, we speculated that ALSap-5 can simultaneously interfere with the las and rhl systems. High-affinity aptamers against HSL in this study are novel QS and virulence-inhibitors, and may have potential as drug candidates for the treatment of P. aeruginosa infection.